Biópsia pulmonar orientada por videotoracoscopia em caes: estudo experimental - Alysson Rodrigo Lamounier (2006)
The purpose of this study was to demonstrate the efficacy of videothoracoscopy in order toobtain lung biopsy specimens in dogs. The sample study consisted of 11 dogs went througha physical exam, thoracic radiographs, hematological and biochemical profiles. Theanesthesia protocol used consisted of acepromazine, butorphanol and diazepam as preanesthesiamedication and propofol and isofluorane for induction and managementanesthetic respectively. Before the lung biopsy, a broncho-alveolar lavage using abronchoscopy was done. In order to collect the lung biopsy and to realize thevideothoracoscopy procedure, two incisions in the right side of thorax were made, one inthe tenth intercostal space and the other in the sixth intercostal space for endoscopy andbiopsy grasping, respectively. Two aleatory lung samples were collected from each dog.The animals were closely evaluated two times a day to verify corporal temperature,respiratory rate and pattern, cardiac rate, subcutaneous emphysema, hematoma, seroma,infection and suture dehiscence. The sutured area was palpated to verify the animalsreaction. In the seventh day after surgery, the dogs were euthanized and submitted tonecropsy where there were taken bilateral lung samples to histopathological examination.The histopathological evaluation in both samples taken by thoracoscopy and necropsy weresame, showing the thoracoscopy is an effective method for evaluating lung pathology